EPC Agenda 2004-09-30 - Academic Senate:::::::::
Educational Policies Committee. Chair Report. Agenda – item added: APARC Priority Recommendations – Approved. Minutes of 4/16/2020 – Approved. President Report. Provost Report. Revision to the Withdrawal Policy – Second Reading – amended and approved. Vice Chair Report. Vice President of Administration and Finance Report. Vice President for Student Affairs Report. Associated Students Report. From FSAC: Policy revision: RTP policy - G. Levels and Sequence of RTP Review #2 and #3 – First Reading completed. Statewide Senator Report. Staff Representative Report. APARC Report. EPC Report. Internship Policy - First Reading completed. FSAC Report. Special Report: Graduation Initiative Group. APARC Priority Recommendations for AY 20-21 – First Reading completed. SAC Report. CFA Report. Good of the Order.